Pemberdayaan Perempuan Melalui Pembentukan Kelompok Wanita Tani “Melati” Desa Karang Binangun Kecamatan Belitang Madang Raya - Tri Rahayu; Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2026)
Women's empowerment is an effort to increase family income, leading to an improvement in the quality of life and independence for women. One of the empowerment efforts for women is carried out through the agricultural sector, such as the